Pine Nursery Soil Test Information Sheet - Rao Mylavarapu; William d'Angelo; Nancy Wilkinson (EDIS, 2009)
Revised! SL-132, a 1-page illustrated fact sheet by Rao S. Mylavarapu, William d'Angelo, and Nancy Wilkinson, is the Pine Nursery Test Form used by the UF/IFAS Extension Analytical Services Laboratories. The sheet gives details about collecting samples and testing fees. Published by the UF Department of Soil and Water Sciences, February 2009.